Effectiveness Of The Blended Learning Method In Enhancing Human Resource Capacity In The Basic Training Program For Civil Servant Candidates (Latsar CPNS) Grade III At The Ministry Of Home Affairs - Shabilla Fieldza Paramitha (Dinasti Publisher, 2026)
This study aims to analyze and describe the effectiveness of the blended learning method in improving technical competencies and fostering core values of the State Civil Apparatus (ASN) in the Basic Training Program for Civil Servants (LATSAR CPNS) Grade III at the Ministry of Home Affairs. The research is motivated by the need to enhance the quality of ASN human resources who are not only technically competent but also able to internalize fundamental values through adaptive learning approaches. This research uses a qualitative descriptive method. Data were collected through interviews, observations, and documentation involving organizers, instructors, and training participants. The results show that the implementation of blended learning is generally effective. This effectiveness is reflected in the suitability of learning levels with participant characteristics, quality of learning materials, proportional time allocation, and institutional support. However, several challenges remain, particularly in technical aspects such as internet connectivity and varying levels of participant engagement. In conclusion, blended learning is effective in improving competencies and supporting ASN value internalization, although improvements in infrastructure and online learning quality are still needed